P-26 Doctors' attitudes towards not for resuscitation orders. (1st September 2015) - Sritharan, G; Levinson, M; Mills, A; Gellie, A
Abstract : Background: An attempt to resuscitate after cardiac/respiratory arrest is mandatory in Australian hospitals, unless there is documentation in the medical history of a decision to not attempt cardiopulmonary resuscitation (CPR). The outcome of CPR in the elderly, chronically ill has been well documented to be very poor. As part of evidence based patient-centred care CPR should only be offered to those for whom it is beneficial. Aim: This study aims to examine doctors' general attitudes towards the discussion and writing of not for resuscitation (NFR) orders; and identify the potential barriers to the completion NFR orders for hospital inpatients. Methods: All doctors accredited at Cabrini Health, Melbourne, Australia were asked to participate in an anonymous online questionnaire. The questionnaire employed likert scales and open-ended questions to gauge physician responses to the legal, ethical, family, personal and cultural/religious issues surrounding the discussion and writing of NFR orders. Results: 107 doctors participated in the study. Doctors are comfortable in writing NFR orders and believe that NFR orders do not result in suboptimal care. In practice, doctors thought the presence of an NFR altered the care delivered by nursing staff including differences in delivery of pain relief, nursing observations and MET calls; and the likelihood of the patient having a procedure/operation. Discussion: NFR orders result in changes to treatment goals of care, suggesting a confounding of NFR orders with the delivery of palliative care. Conclusion: There are complex barriers to the writing and implementation of NFR orders, complicated by doctors' views on the relationship with goals of care.